KEDUDUKAN KONSTITUSI DALAM PRAKTIK KETATANEGARAAN SAUDI ARABIA - Nur Rohim (TAHKIM, 2013)
Almost no country that does not have the current constitution. This indicates that the constitution is an absolute must exist in a country, although there are some States that make it as an unwritten constitution. Similarly, Saudi Arabia Monarky Absolut shaped, although the provisions of the basic law states (constitutional) state is al-Quran and al-Sunnah, but in its application to put forward the decree of the king as the main source of law. Interestingly, there was a decree issued by King Fahd king in the year 1412 AD H/1992 as The Basic Law of Government named an al-Nidzam al-Asasi lil Hukmi terms and conditions that meet the elements of the constitution. Even henceforth serve as the primary basis in constitutional Saudi Arabia, such as General Principles, Systems Administration, Member of the Saudi Society, Principles of Economics, Rights and Obligations, State Power, Financial Affairs, Audit and Control Authority, and the General Assessment. Even after the decree is also used as the basis for the kings decree. Keywords: Constitution, Decree of the King, constitutional